Efektivitas Penggunaan Kamus Arab dalam Meningkatkan Kosakata Siswa SMK Tarbiyatus Salafiyah Pesawahan (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the effectiveness of using an Arabic dictionary in enhancing the vocabulary of students at SMK Tarbiyatus Salafiyah Pesawahan Tiris Probolinggo. The main focus of this research is to identify the factors influencing the use of dictionaries in vocabulary acquisition and the impacts resulting from their use. The research problem formulation includes identifying the supporting and inhibiting factors in dictionary utilization and analyzing the effects of dictionary use on students’ vocabulary mastery. This study employs a qualitative descriptive approach. Data were collected through direct classroom observation to examine students’ interactions with dictionaries, in-depth interviews with students and educators to explore their experiences and perceptions, and documentation in the form of field notes and student work to analyze vocabulary development. The findings indicate that the effectiveness of dictionary use is influenced by both inhibiting and supporting factors. Inhibiting factors include the limited availability of dictionaries, a lack of understanding regarding their proper use, and restricted access to digital technology. Meanwhile, supporting factors involve teachers’ patience in providing guidance, students’ high enthusiasm and motivation, and their Arabic language proficiency. The positive impact of effective dictionary use is not limited to an increase in vocabulary acquisition but also contributes to students’ confidence in communicating in Arabic, enhances memory and cognitive skills, and improves reading and writing abilities. Thus, this study concludes that using Arabic dictionaries is effective in enriching students’ vocabulary, especially when supported by conducive factors.